(untitled) (Ius Novum, 2025)
The article analyses the type of behaviour of arbitrary separation in terms of its division between criminal law and misdemeanour law. This behaviour has been considered bitype since the entry into force of the Act of 11 March 2022 on Homeland Defence (i.e. since 23 April 2022), but not to its full substantive scope. Halving only applies to the arbitrary leaving of a designated place of residence and does not cover criminal behaviour consisting in the arbitrary leaving of an entity – which should be criticised. In this article, in order to provide a comprehensive approach to the analysed issues, the historical outline of the penalisation of the crime of arbitrary separation is presented, and de lege ferenda tasks are set, the implementation of which will result in, among others: removing the loophole in the law in the form of total impunity for one-off, arbitrary separation of a soldier from their unit, lasting no more than 48 hours, which has been present in the military criminal law system continuously since 1 January 2010, i.e. since the entry into force of the amendment changing, among others, the wording of the provision of Article 338 of the Penal Code.